Gender Differences in Patients With COVID-19: Focus on Severity and Mortality - Jin, Jian-Min; Bai, Peng; He, Wei; Wu, Fei; Liu, Xiao-Fang; Han, De-Min; Liu, Shi; Yang, Jin-Kui (Frontiers in Public Health, 2020)
Objective: The recent outbreak of Novel Coronavirus Disease (COVID-19) is reminiscent of the SARS outbreak in 2003. We aim to compare the severity and mortality between male and female patients with COVID-19 or SARS. Study Design and Setting: We extracted the data from: (1) a case series of 43 hospitalized patients we treated, (2) a public data set of the first 37 cases of patients who died of COVID-19 and 1,019 patients who survived in China, and (3) data of 524 patients with SARS, including 139 deaths, from Beijing in early 2003. Results: Older age and a high number of comorbidities were associated with higher severity and mortality in patients with both COVID-19 and SARS. Age was comparable between men and women in all data sets. In the case series, however, men's cases tended to be more serious than women's (P = 0.035). In the public data set, the number of men who died from COVID-19 is 2.4 times that of women (70.3 vs. 29.7%, P = 0.016). In SARS patients, the gender role in mortality was also observed. The percentage of males were higher in the deceased group than in the survived group (P = 0.015). Conclusion: While men and women have the same prevalence, men with COVID-19 are more at risk for worse outcomes and death, independent of age.